2009
DOI: 10.1159/000205583
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mammalian Chitinases in Asthma

Abstract: Asthma is a chronic inflammatory disease characterized by airway inflammation, mucus hypersecretion and airway hyperresponsiveness. Mechanisms underlying the pathogenesis of asthma are not fully understood. In recent years, there are mounting evidences demonstrating that mammalian chitinases may play a key role in mediating the T-helper 2 cell-driven inflammatory response that is commonly associated with asthma. Chitinases (e.g., chitotriosidase and acidic mammalian chitinase) are enzymes that degrade chitin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 88 publications
(54 reference statements)
0
61
0
4
Order By: Relevance
“…Increased expression of these proteins has been associated with inflammatory diseases, in particular with allergic asthma (reviewed in (Lee et al, 2008;Shuhui et al, 2009). The physiological function of Ym1 is not clear, but a role in eosinophil chemotaxis (Owhashi et al, 2000) and promotion of cytokine production (Cai et al, 2009) has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of these proteins has been associated with inflammatory diseases, in particular with allergic asthma (reviewed in (Lee et al, 2008;Shuhui et al, 2009). The physiological function of Ym1 is not clear, but a role in eosinophil chemotaxis (Owhashi et al, 2000) and promotion of cytokine production (Cai et al, 2009) has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of studies on chitinase have been conducted on microorganisms [12], chitinase is also found and has been investigated in many other biological species, including mammals [13]- [15], fish [16]- [19], mollusks [20] [21], insects [22]- [24], plants [22] [25], and fungi [1] [22]. Since the physiological role of chitinase varies in these organisms, the mechanism and efficiency of chitinase degradation and the substrate specificity have been reported to vary.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, acidic mammalian chitinase expressed in the stomach of mammals [26], and chitotriosidase produced by macrophages [14] [15] are thought to function in the digestion and absorption of food and defense against pathogens. In addition, chitinase has been detected at the onset of asthma and allergies, suggesting its involvement in diseases [13] [15]. In contrast, chitinase and Hex are also found in the digestive tracts of fish.…”
Section: Introductionmentioning
confidence: 99%
“…Since it was identified in 1993 as a secreted product of articular chondrocytes and synovial cells (9), a growing body of evidence has shown that high serum levels of YKL-40 are associated with various pathological conditions such as allergic diseases (10)(11)(12). In terms of lung diseases, high serum levels of YKL-40 are associated with asthma (13,14), chronic obstructive pulmonary disease (15), and lung cancer (16).…”
mentioning
confidence: 99%